Adaptation and validation of the Moroccan Arabic version of the Psychosocial Impact of Dental Aesthetics Questionnaire (PIDAQ) - F. Bourzgui; Z. Serhier; M. Sebbar; S. Diouny; M. Bennani Othmani; P.I. Ngom (Saudi Dental Journal)
Objective: The aims of this study were to translate and culturally adapt the PIDAQ native English version into Moroccan Arabic, and to assess the psychometric characteristics of the version thereby obtained. Materials and methods: The PIDAQ original English version was sequentially subjected to translation into Moroccan Arabic, back-translation into English, committee review, and pre-testing in 30 subjects seeking orthodontic treatment. Results: The final Moroccan Arabic version further underwent an analysis of psychometric properties on a random sample of 99 adult subjects (84 females and 15 males, aged 20.97 ± 1.10 years). The intraclass coefficient correlation of the scores of the responses obtained after administration of the questionnaire twice at a 1-month interval to a random sample of 30 subjects ranged from 0.63 for “Self-confidence” to 0.85 for “Social Impact”. Cronbach α coefficients ranging from 0.78 for “Aesthetic Concerns” to 0.87 for “Self-confidence” were obtained; the different subscales of the Moroccan Arabic version of the PIDAQ showed good correlation with the perception of aesthetics and orthodontic treatment need. Conclusion: The results of the present study indicate that the Moroccan Arabic version of the PIDAQ obtained following thorough adaptation of the native form is both reliable and valid. It is able to capture self-perception of orthodontic aesthetic and treatment need and is consistent with normative need for orthodontic treatment. Keywords: The Psychosocial Impact of Dental Aesthetics Questionnaire, Orthodontics, Quality of life, Adaptation and validation, Moroccan Arabic